2005
DOI: 10.1128/aem.71.6.2862-2869.2005
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Nucleus-Encoded Chitinase from the Yeast Kluyveromyces lactis

Abstract: Endogenous proteins secreted from Kluyveromyces lactis were screened for their ability to bind to or to hydrolyze chitin. This analysis resulted in identification of a nucleus-encoded extracellular chitinase (KlCts1p) with a chitinolytic activity distinct from that of the plasmid-encoded killer toxin ␣-subunit. Sequence analysis of cloned KlCTS1 indicated that it encodes a 551-amino-acid chitinase having a secretion signal peptide, an amino-terminal family 18 chitinase catalytic domain, a serine-threonine-rich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…Our study revealed a role of chitinases in cell separation of yeast cells in U. maydis. Such a function of chitinases has already been described in ascomycetes (reviewed in references 12 and 49), e.g., in the model yeast S. cerevisiae (11), the opportunistic pathogen Candida albicans (10), and the industrially used yeast Kluyveromyces lactis (50). In these species, single deletions of the corresponding chitinase lead to cell aggregation.…”
Section: Discussionmentioning
confidence: 99%
“…Our study revealed a role of chitinases in cell separation of yeast cells in U. maydis. Such a function of chitinases has already been described in ascomycetes (reviewed in references 12 and 49), e.g., in the model yeast S. cerevisiae (11), the opportunistic pathogen Candida albicans (10), and the industrially used yeast Kluyveromyces lactis (50). In these species, single deletions of the corresponding chitinase lead to cell aggregation.…”
Section: Discussionmentioning
confidence: 99%
“…1A). The C-terminal sequence of Cts1 encodes a type-2 chitin binding domain that is not present in the Candida chitinases (Colussi et al, 2005;Kuranda and Robbins, 1991). Located in the C-terminal sequence of Cht2 is a potential GPI-anchor site that is not found in the other S. cerevisiae or C. albicans chitinases (analysis with DGPI software at http:// 129.194.185.165/dgpi/index_en.html).…”
Section: Comparison Of Chitinase Genesmentioning
confidence: 98%
“…The Candida albicans genome contains three chitinase genes, CHT1 , CHT2 , and CHT3 , which are homologous to the Saccharomyces cerevisiae CTS1 gene and C. albicans CHT4 , which is homologous to S. cerevisiae CTS2 (Dunkler et al, 2005). Recently a nucleus encoded chitinase (KlCts1p) has been characterized from yeast Kluyveromyces lactis (Colussi et al, 2005 ). This species is an industrially important yeast species due to its ability to grow to a high cell density and abundantly secrete heterologous protein (Rocha et al, 1996 ).…”
Section: Production Of Yeast Chitinasesmentioning
confidence: 99%